Quadriceps or patellar ligament reconstruction with artificial ligament after total knee replacement - Ponziani, Lorenzo; Tentoni, Francesco; Di Caprio, Francesco (Acta Biomedica Atenei Parmensis, 2022)
Background and aim of the work: Ruptures of the quadriceps or patellar tendon after TKA implantation are a fearful and disabling complication. Direct reconstructions highlighted various problems, such as the decrease in extensor force, failure, need for prolonged post-operative immobilization. So augmentation techniques have been proposed with autologous tendons, allografts, artificial ligaments. Among these, the LARS seems the most modern and promising. For this reason, we have retrospectively reviewed a case series patients operated with this artificial ligament, to evaluate the results and highlight the tips and tricks for this procedure. Methods: Ten patients with a mean age of 69.4 years suffered an extensor apparatus lesion after knee replacement. These patients underwent primary reconstruction and augmentation with LARS. They were retrospectively reviewed at a mean follow-up of 3.8 years, by measuring active flexion and extension, and by Lysholm scoring scale. Results: We did not observe any problems with healing of the surgical wound, nor phenomena of intolerance to the implanted material, such as inflammation, skin rashes or fistulas. The mean flexion was 117 degrees. Active extension was allowed in all patients, but with a mean extensor lag of 18 degrees. The mean Lysholm score was 74.2. Conclusions: LARS offers good results without completely solving the problem of extensor lag, linked to the softness of the tissues in the quadriceps. The major advantages of LARS reside in the good tissue ingrowth, the absence of adverse tissue reactions, the ubiquitous availability, the possibility of stable fixation with early rehabilitation.